Influence of maleated elastomer on filler dispersion, mechanical and antimicrobial properties of hybrid HDPE/clay/silver nanocomposites. Issue 9 (2nd May 2016) - Sanchez-Valdes, Saul
Abstract: This work analyses the effect of using ethylene-propylene-diene-monomer-grafted maleic anhydride (EPDM-g-MA) as compatibilizer to improve the interfacial properties and toughness of high-density polyethylene–organoclay–silver (HDPE/clay/silver) nanocomposites. EPDM-g-MA was reacted using ultrasound with a solution of AgNO3 0.04 M and ethylene glycol using ammonium hydroxide to obtain the silver ammonium complex. This silver-coated maleated EPDM was then melt mixed with HDPE and organoclay (Nanomer I28E) using a twin-screw extruder. Transmission electron microscopy (STEM) and X-ray diffraction (XRD) results confirmed the filler dispersion of both organoclay and silver nanoparticles into HDPE matrix when maleated EPDM was used. Both fillers were better dispersed and exfoliated by using this compatibilizer. The thermal stability enhancement of nanocomposites was confirmed using thermogravimetric analysis. Mechanical and antimicrobial properties demonstrated that better dispersed filler obtained with maleated EPDM enhanced the toughness and antimicrobial behaviour of HDPE/clay/silver hybrid nanocomposites. This confirmed that maleated EPDM was an efficient compatibilizer to obtain hybrid nanocomposites with enhanced properties to be used for several HDPE applications.